2016
DOI: 10.1371/journal.pone.0163938
|View full text |Cite
|
Sign up to set email alerts
|

There’s More to Groove than Bass in Electronic Dance Music: Why Some People Won’t Dance to Techno

Abstract: The purpose of this study was to explore the relationship between audio descriptors for groove-based electronic dance music (EDM) and raters’ perceived cognitive, affective, and psychomotor responses. From 198 musical excerpts (length: 15 sec.) representing 11 subgenres of EDM, 19 low-level audio feature descriptors were extracted. A principal component analysis of the feature vectors indicated that the musical excerpts could effectively be classified using five complex measures, describing the rhythmical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“… 47 ). Accordingly, syncopation is perceived as more prominent when produced by a bass drum than a hi-hat cymbal ( 48 ), and rhythmically complex bass lines are rated as increasingly likely to make people dance ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“… 47 ). Accordingly, syncopation is perceived as more prominent when produced by a bass drum than a hi-hat cymbal ( 48 ), and rhythmically complex bass lines are rated as increasingly likely to make people dance ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results on beat salience were largely confirmed by Stupacher et al in 2016 [ 77 ] who additionally found that high sound intensity in the lowest bass range was positively associated with groove. Also in 2016, Wesolowski & Hofmann [ 78 ] studied 198 excerpts from electronic dance music and found that stimuli with a non-isochronous bass and high rhythmic variability in the upper frequency domain were positively evaluated by listeners, compared to stimuli that did not show these characteristics. Finally, in a recent study, Etani et al [ 79 ] found that the groove experience was influenced by the tempo of the music.…”
Section: Introductionmentioning
confidence: 99%
“…The role of taste has rarely been considered in the context of groove studies, and the few results were inconsistent: Butterfield [ 62 ] observed in 2010 that, in his experiment, listeners’ taste in music did not influence their perception of microtiming. Yet, Wesolowski & Hofmann [ 78 ] showed in 2016 that musical preference affected groove ratings significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic dance music (EDM), which is commonly played during dance events, is quantised. In EDM, other musical properties like syncopation or timbre variations were found to have a positive effect on the motivation of listeners to move or dance to the music (Wesolowski & Hofmann, 2016 ; Witek, Clarke, Wallentin, Kringelbach, & Vuust, 2014 ). Timbre variations and syncopation can also be found in jazz performances, and today listeners are used to dancing to quantised music.…”
Section: Introductionmentioning
confidence: 99%